Otoritas Guru Dalam Prestasi Belajar Siswa Menggunakan Fuzzy Mamdani - Desyanti Desyanti; John Suarlin; Rudi Faisal (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Education is a systematic effort to create good learning conditions in increasing one's potential to have good knowledge, but in the teaching and learning process one often finds students who cannot achieve achievements in accordance with their intelligence and also the teacher's attitude in teaching and educating. The teaching and learning process is sometimes less effective, teachers tend to provide material using books and blackboards, thereby reducing students' interest in learning and affecting their learning achievement. Teachers have a huge influence on each student's development, but not all teachers are able to exercise their authority in the classroom. Teachers will be able to exercise their authority if they have good teaching skills. The use of fuzzy mamdani is able to calculate the extent of the teacher's authoritative relationship to student learning achievement based on the assessment data carried out. Based on the research results, the level of authority is divided into 3 membership functions (Bad, Fair, Good), from this data the highest value is 0.74 in the good membership function, 0.25 is sufficient and 0.00 is bad. So the category of the level of relationship between teacher authority and student learning achievement with a score of 84.95 is in the Good category. The value obtained from the calculation results can be a benchmark for the teacher's attitude and upbringing towards students.